Correction: Study of Public Space Use and Design based on Japanese and Foreign Perceptions - Dini Hardilla; Bart Dewancker (Environmental Science and Sustainable Development)
Public space will be studied regarding history, use, and the evolution of urban space. Through culture, architecture, and behavior, this paper investigates how Japanese and foreigners use public space. Foreigners use open spaces such as neighborhood parks more frequently than Japanese people, who consider space sacred and private. Because of this study, urban space will be analyzed from the perspective of Japanese culture and customs as well as foreign culture to qualify the precise meaning of space, urban space, and cultural space, within the context of diverse conditions and ethnicities. Residents who frequently use neighborhood parks recognize that foreigners are more welcome and that spatial accessibility contributes to the creation of a unifying space in their neighborhoods. Understanding cultural views and ethnic behavior is critical to the design and implementation of effective and creative urban spaces.